Local Wisdom Values of Sea Alms Tradition in Tanjungan Rembang Village as a Source of Learning History - Muhammad Jodi Prasetiyo; Millatul Lailiyah; Destina Marta Fiani; Putri Suryaningsih; Yusrotin Meila Rizqina (JURNAL PENDIDIKAN IPS, 2023)
The Sea Alms Tradition is a way of expressing the gratitude of local fishermen to God. The marine alms meant to ask for the protection of fishermen so that they are given welfare at sea. This study aims to explain the practice of carrying out the almsgiving ceremony in tanjungan village, Kragan sub-district, Rembang district and to find out the local wisdom values of the sea alms tradition in history lessons. This type of research is field research, which is carried out by going directly to the field to obtain data related to the tradition of the sea alms ceremony in Tanjungan village. In addition, this research is a qualitative research because in this research it describes the facts as a whole through data collection in the field. The results of the study show that the alms-alms tradition as a source of learning history is because there are moral messages in the alms-alms tradition that can support history learning, especially in discussing the historical traditions of Indonesian society. Apart from that, in the marine alms tradition in Tanjungan Village there are also social values that can be learned in the form of mutual cooperation, tolerance, sincere charity, and social care.